Designing Educational Games for Teaching Hydro-Electric Power Stations in Elementary School Curriculum - Muliyati, Dewi; Firdaus, Bagaskara (Current STEAM and Education Research, 2024)
Introducing the concept of renewable energy to elementary school students is very important, one of which is to enhance their learning motivation. In enhancing learning motivation, it is necessary to have enjoyable, interactive, and easy-to-use learning media so that elementary school students feel happy while studying a subject. In this study, we present a novel approach to teaching elementary school students about hydro-electric power stations through the development of an android-based game. The game is designed to gamify the learning process, engaging students in an interactive and immersive experience that facilitates understanding of complex concepts related to hydro-electric power generation. Our focus lies in elucidating the manufacturing, construction, operational procedures, and supplementary information pertinent to hydro-electric power stations within a format accessible to elementary students. By harnessing the capabilities of Unity 3D software and incorporating assets from Obi Fluid, we have crafted an engaging and educational gaming application tailored to the unique learning needs of young learners. This research contributes to the growing body of literature on educational game design and underscores the potential of gamified approaches in enhancing STEM education at the elementary level. Furthermore, it lays the groundwork for future studies exploring the effectiveness of similar interventions in diverse educational contexts.